Особливості відтворення національно-культурного колориту поетичної мови Тараса Шевченка в перекладах на близькоспоріднені мови - Зайченко, Неоніла; Паламарчук, Ольга; Шевченко, Мирослава; Zaychenko, Neonila; Palamarchuk, Olga; Shevchenko, Myroslava (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано мовні відхилення від оригінального тексту балади Тараса Шевченка «Тополя» при відтворенні в перекладах на інші слов’янські мови її національно-культурного колориту, а також з’ясовано причини таких відхилень в аспекті міжмовної та міжкультурної взаємодії. Language deviations from the original text of Taras Shevchenko’s ballad “Poplar” while reflecting its national and cultural colour in translations into Byelorussian, Bulgarian, Russian, Slovak and Czech languages have been analysed in the article as well as causes of the referred deviations within the aspect of interlingual and intercultural asymmetry have been followed; units of different language levels, which helps to verbalize the culturological information of original text, words with national and cultural semantic component – liguorealia and background and connotative vocabulary have been considered. System, structural and functional peculiarities of each target language in regard to source Ukrainian language as well as specific development character of their figurative and sense, background and connotative and stylistic unit meanings of different levels are deemed to be an objective factor for motivated deviations while reflecting the national and cultural colour of original text. Unmotivated language deviations are caused by human factor – personality of translator, level of his/her professional competence and poetic talent.
Reflection Peculiarities of National and Cultural Colour of Taras Shevchenko’s Poetic Language in Translations into Closely Related Languages.
Keywords: національно-культурний колорит; переклад; міжкультурна і міжмовна асиметрія